2012
DOI: 10.1042/cbi20120274
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cyclin A, B1 and D1 after induction of cell cycle arrest in the Jurkat cell line exposed to doxorubicin

Abstract: Jurkat human lymphoblastoid cells were incubated in increasing concentrations of doxorubicin (0.05, 0.1 and 0.15 μM) to induce cell death, and their expression of cyclin A, B1 and D1 was evaluated by flow cytometry (cell cycle progression, Annexin V assay, percentages and levels of each of the cyclins), transmission electron microscopy (ultrastructure) and confocal fluorescence microscopy (expression and intracellular localization of cyclins). After low-dose doxorubicin treatment, Jurkat cells responded mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 35 publications
(38 reference statements)
1
4
0
1
Order By: Relevance
“…Therefore, it would be tempting to hypothesize that increased levels of cyclin D1 may somehow reflect or even promote these cells to enter the S phase and proliferate further, especially as we have shown in our cyclin D1/PI double staining experiment that the highest levels of cyclin D1 are indicative of G2/M population and particularly of the fraction of polyploid cells. In previous studies we also found that the levels/fluorescence of cyclin D1 increased in the G2/M and polyploidy after treatment with doxorubicin in the Jurkat and A549 cell lines (Żuryń et al, ; Litwiniec et al, ). The percentage of subG 1 fraction as well as early and late apoptotic cells, as evidenced by annexin V/PI staining, is visibly increased starting from this concentration and the number of G0/G1‐cyclin D1‐positive cells decreased, whereas the respective values were also reduced in the S‐ and G2/M‐phases with 0.3 µM doxorubicin, which suggests that induction of cell death pathways most probably contribute to observed reductions in the number of polyploid cells.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, it would be tempting to hypothesize that increased levels of cyclin D1 may somehow reflect or even promote these cells to enter the S phase and proliferate further, especially as we have shown in our cyclin D1/PI double staining experiment that the highest levels of cyclin D1 are indicative of G2/M population and particularly of the fraction of polyploid cells. In previous studies we also found that the levels/fluorescence of cyclin D1 increased in the G2/M and polyploidy after treatment with doxorubicin in the Jurkat and A549 cell lines (Żuryń et al, ; Litwiniec et al, ). The percentage of subG 1 fraction as well as early and late apoptotic cells, as evidenced by annexin V/PI staining, is visibly increased starting from this concentration and the number of G0/G1‐cyclin D1‐positive cells decreased, whereas the respective values were also reduced in the S‐ and G2/M‐phases with 0.3 µM doxorubicin, which suggests that induction of cell death pathways most probably contribute to observed reductions in the number of polyploid cells.…”
Section: Discussionsupporting
confidence: 52%
“…Cyclin D1 plays a crucial role in tumorigenesis, which propels cell cycle progression at the G1/S stage and promotes the proliferation of cancer cells [18,19]. As a result, it is also recommended as an important biomarker of pathological diagnosis and therapy for different cancers [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, different levels of doxorubicin dose produced different cell death pathways, and lower doses may induce G2/M arrest (28,29). To investigate whether fulvestrant also enhanced doxorubicin-induced G2/M arrest, cell cycle distribution was analysed by flow cytometric assay (Fig.…”
Section: Resultsmentioning
confidence: 93%